Post-elimination surveillance in formerly onchocerciasis endemic focus in Southern Mexico - Fernández-Santos, Nadia A.; Unnasch, Thomas R.; Rodríguez-Luna, Isabel C.; Prado-Velasco, Francisco Gibert; Adeniran, Adebiyi A.; Martínez-Montoya, Humberto; Rodríguez-Pérez, Mario A. (PLOS Neglected Tropical Diseases, 2020)
Background All formerly endemic communities of the Southern Chiapas focus of onchocerciasis in Mexico were treated with ivermectin until parasite transmission was eliminated by 2015. Transmission of onchocerciasis did not resume during a period of three years (2012–2014) following the final distribution of ivermectin in 2011; it was thus concluded that transmission remained undetectable without intervention. WHO thus declared the elimination of transmission of onchocerciasis from Mexico in 2015. Methodology/Principal findings From 2016 to the present, post-elimination surveillance (PES) based on examination for suspected onchocercomas was performed in the former Southern Chiapas focus. Each year, over 60% of the total population (range = 85,347–104,106 individuals) of the formerly endemic communities were examined for onchocercomas. Thirty-four individuals were found harboring suspected onchocercomas in the PES surveys conducted from 2016–2019. Of these, one female of 7 years of age who had immigrated from a formerly endemic focus, harbored an infertile (sterile) female in the suspected onchocercoma; all others were negative. Skin biopsy assessments were performed from March through May 2017 in three communities where the female resided. None of the 83 individuals of the three communities examined by skin biopsy were mf positive. Similarly, none of the biopsies from the individuals were found to contain parasite DNA when tested by polymerase chain reaction-enzyme-linked immunosorbent assay (PCR-ELISA). Conclusions/Significance These provide support to the conclusion that onchocerciasis has been eliminated from Mexico.